Global patterns of intraspecific leaf trait responses to elevation. (6th May 2019) - Midolo, Gabriele; De Frenne, Pieter; Hölzel, Norbert; Wellstein, Camilla
Abstract: Elevational gradients are often used to quantify how traits of plant species respond to abiotic and biotic environmental variations. Yet, such analyses are frequently restricted spatially and applied along single slopes or mountain ranges. Since we know little on the response of intraspecific leaf traits to elevation across the globe, we here perform a global meta‐analysis of leaf traits in 109 plant species located in 4 continents and reported in 71 studies published between 1983 and 2018. We quantified the intraspecific change in seven morpho‐ecophysiological leaf traits along global elevational gradients: specific leaf area (SLA), leaf mass per area (LMA), leaf area (LA), nitrogen concentration per unit of area (N area ), nitrogen concentration per unit mass (N mass ), phosphorous concentration per unit mass (P mass ) and carbon isotope composition (δ 13 C). We found LMA, N area, N mass and δ 13 C to significantly increase and SLA to decrease with increasing elevation. Conversely, LA and P mass showed no significant pattern with elevation worldwide. We found significantly larger increase in N area, N mass, P mass and δ 13 C with elevation in warmer regions. Larger responses to increasing elevation were apparent for SLA of herbaceous compared to woody species, but not for the other traits. Finally, we also detected evidences of covariation across morphological and physiological traits within the same elevational gradient. In sum, we demonstrate that there are common cross‐species patterns of intraspecific leaf trait variation across elevational gradients worldwide. Irrespective of whether such variation is genetically determined via local adaptation or attributed to phenotypic plasticity, the leaf trait patterns quantified here suggest that plant species are adapted to live on a range of temperature conditions. Since the distribution of mountain biota is predominantly shifting upslope in response to changes in environmental conditions, our results are important to further our understanding of how plants species of mountain ecosystems adapt to global environmental change. Abstract : We conducted a meta‐analysis on the intraspecific leaf trait variation along elevation in 109 plant species across 92 elevational transects located in 4 continents and reported in 71 studies. We found that there are common patterns of intraspecific leaf trait variation across different plant species and mountain ranges of the world. Since the distribution of mountain biota is predominantly shifting upslope in response to changes in environmental conditions, our results are important to further our understanding of how plants species of mountain ecosystems adapt to global environmental change.